Characterization of 2,2-DCP degrading ability of halotolerant bacteria and its dehalogenase structural analysis - Mohamed Faraj Abdulgader Edbeib, 1985-, author; Roswanira Abdul Wahab, supervisor; Fahrul Zaman Huyop, 1971-, supervisor; Fakulti Biosains dan Kejuruteraan Perubatan (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Ph.D (Biosains)) - Universiti Teknologi Malaysia, 2017